Determinants of employee retention in UiTM Holdings Sdn Bhd / Mohammad Razi Afnan Rosdi - Rosdi, Mohammad Razi Afnan (Faculty of Business and Management, 2018)
The employee retention is a continuous problem or issues that always be a major issue of any company. The purpose of this research were to examine the relationship between independent variables (training and development program, work life balance, promotional opportunities and employee recognition) and dependant variables (employee retention) in UiTM Holdings Sdn Bhd and to identify the most influence factor on employee retention in the company. The sample size of the research is 103 out of 140 total of population comes from Human Resource Department, Finance department, Risk Management Department, Procurement and IT Department. Researcher use simple random sampling as the collection of information is randomly pickup from the selected respondents among the total population in the company. Researcher used questionnaire as the method to collect all the data from the respondents in accomplishing the research objectives. This study is beneficial to the companies in Malaysia especially in situation where they are facing high employee turnover. It will helps them to gain awareness on the main factors and manage the issue from getting worse. The discussions and recommendations for future research are also have been discussed in chapter